Study of a fluid flow problem in front of a circular cylinder - Fellak, Alaeddine; Blizak, Taha: Supervisor (Mohamed Boudiaf University of M'sila, Faculty of Mathematics and Informatics, Department of Mathematics, 2024)
In this memory, we have discussed two fundamental subjects. The initial topic revolves around the fluid flow around a circular cylinder without considering the impact of gravity and surface forces. To analyze this, we have employed conformal transformations and current lines. The second topic focuses on the fluid flow around a circular cylinder, considering the surface flow. To examine this, we have utilized conformal transformations and the series truncation method.
Keywords: Free surface; potential; current lines; series truncation; surface tension; Weber number